2019
DOI: 10.1111/jep.13204
|View full text |Cite
|
Sign up to set email alerts
|

Linking hospital culture to the training performance of residents: The roles of leader‐member exchange and transactional leadership style

Abstract: Background: Hospital culture is a crucial aspect of residents' training. However, the mechanisms related to stakeholder culture (SC) and teacher-resident interaction remain unclear. The study investigated the relationship between hospital culture and training performance of residents. Also, it explored the mediating effect of teacher-resident exchange and the moderating effect of the teacher's transactional leadership style within a Chinese context. Methods: Based on stakeholder and leadership member exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This can be explained through the LMX theory according to which the dyadic exchange developed between leaders and followers is positively associated with job satisfaction (Epitropaki and Martin, 2005;Fazlollahtabar, et al, 2016;Graen and Uhl-Bien, 1995). In the context of medical resident training, LMX has been addressed as teacher resident exchange that leads to enhanced job satisfaction (Vaughn and Baker, 2004;Deng et al, 2020).…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
“…This can be explained through the LMX theory according to which the dyadic exchange developed between leaders and followers is positively associated with job satisfaction (Epitropaki and Martin, 2005;Fazlollahtabar, et al, 2016;Graen and Uhl-Bien, 1995). In the context of medical resident training, LMX has been addressed as teacher resident exchange that leads to enhanced job satisfaction (Vaughn and Baker, 2004;Deng et al, 2020).…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
“…A previous study found that applying LMX theory for training of medical resident physicians at a hospital in China under senior doctor teachers suggests that senior doctors should consider multiple cultures and multiple stakeholders in a single context, emphasize positive relationships and utilize incentives in training new medical residents (Deng et al , 2020). Considering the relationship between senior doctor teachers and new resident physicians is also called teacher–resident exchange (TRX) (Deng et al , 2020). Deng et al.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that applying LMX theory for training of medical resident physicians at a hospital in China under senior doctor teachers suggests that senior doctors should consider multiple cultures and multiple stakeholders in a single context, emphasize positive relationships and utilize incentives in training new medical residents (Deng et al, 2020). Considering the relationship between senior doctor teachers and new resident physicians is also called teacher-resident exchange (TRX) (Deng et al, 2020). Deng et al apply stakeholder theory in that "the development of an organization cannot be separated from the involvement of various stakeholders," which means that stakeholder-related problems in TRX must consider relationships with multiple subjects (Deng et al, 2020).…”
Section: Lmx Theory For New Dentistsmentioning
confidence: 99%
See 2 more Smart Citations